#TITLE_ALTERNATIVE# - ARIA UTAMA (NIM: 30312001), JUDHISTIRA
The success of Yarkovsky effect in explaining gap between observations and Classical Model (CM) predictions which only relies on the gravity, suggests that the influence of this effect on the orbital evolution of spinning objects of 10 cm - 40 km in diameter can not be ignored. The inclusion of this effect in the study of the dynamics and evolution of Main Belt asteroid population and asteroid families can be found in literatures. Having successfully detected this effect on individual asteroids such as 6489 Golevka (1991 JX), we guess that long-term (in the order of millions to billions years) accumulation of Yarkovsky effect may affect the advanced evolution of the Near-Earth Asteroids (NEAs) population in general. For this purpose we performed a numerical simulation method with Swift_RMVS4y integrator employed on 3372 NEAs sample with well-known orbits. After the first 5 Megayears (Myr) of computation, it was found that the majority of samples ended up as Sun grazers (28%) and were thrown to the outer part of the Solar System (23.5%) came from the Apollo and Amor classes. Only 4% of the sample population was impacting the terrestrial planets (mainly with Mars, Earth and Venus) and 0.5% with the jovian planets (mainly Jupiter). With the mean fractional decay rate of our NEAs sample to the sinks (collide with the Sun or planets and thrown to the outer Solar System) of -0.1188 +/- 0.0016 per Myr, the entrance flux to these disposal zones is 114 +/- 14 objects per Myr for H < 18 and median lifetime of 3.7 Myr that will be replenished mostly by Intermediate source Mars-crossing Asteroid (IMC) of 71 +/- 17 objects per Myr for H < 18. Especially for Earth-Crossing Asteroids (Apollo and Aten classes), there is a strong indication that during 2 Myr of computation more samples of Aten class population evolved into Apollo (entrance flux: 19 +/- 3 per Myr for H < 18) than the reverse process (entrance flux: 5.0 +/- 0.6 per Myr for H < 18). Other evidence was obtained regarding the influence of thermal effect on NEAs population; the increase of Amor class population instead of Apollo. Utilizing the decay information of IMC population into near-Earth region, we found that the Amor class population gained a supply of greater than 25 more than that of the Apollo class population.We also found (in small number) the formation of a new class of NEAs with orbits entirely inside the orbit of Venus and in a retrograde state. Our study finds that NEAs impact rate with terrestrial planets is increased significantly (up to around 30x higher). The largest impact rate is obtained for planet Earth (4.8x10^-8 yr^-1), which is about 6x greater than Mercury's. The discrepancy between our results with the previous studies is unlikely due to the inclusion of Yarkovsky effect because of the short duration of meta-stable condition provided by resonance in a < 2 au. Utilizing our NEAs sample that ends up as Earth impactor (MOID < Rc), we developed a mathematical model to predict the asteroid diameter required to form a specific impact crater. For craters larger than 100 km our model predicts smaller asteroid is required that is in agreement with the Iridium analysis estimation.